Population genetic analysis of Theileria parva isolated in cattle and buffaloes in Tanzania using minisatellite and microsatellite markers - Rukambile, E.; Machuka, J.; Njahira, Moses N.; Kyallo, Martina M.; Skilton, Robert A.; Mwega, E.; Chota, A.; Mathias, M.; Sallu, R.; Salih, Diaeldin A. (Elsevier, 2016)
A population genetic study of Theileria parva was conducted on 103 cattle and 30 buffalo isolates from Kibaha, Lushoto, Njombe Districts and selected National parks in Tanzania. Bovine blood samples were collected from these study areas and categorized into 5 populations; Buffalo, Cattle which graze close to buffalo, Kibaha, Lushoto and Njombe. Samples were tested by nested PCR for T. parva DNA and positives were compared for genetic diversity to the T. parva Muguga vaccine reference strain, using 3 micro and 11 minisatellite markers selected from all 4 chromosomes of the parasite genome. The diversity across populations was determined by the mean number of different alleles, mean number of effective alleles, mean number of private allele and expected heterozygosity. The mean number of allele unique to populations for Cattle close to buffalo, Muguga, Njombe, Kibaha, Lushoto and Buffalo populations were 0.18, 0.24, 0.63, 0.71, 1.63 and 3.37, respectively. The mean number of different alleles ranged from 6.97 (Buffalo) to 0.07 (Muguga). Mean number of effective alleles ranged from 4.49 (Buffalo) to 0.29 (Muguga). The mean expected heterozygosity were 0.07 0.29, 0.45, 0.48, 0.59 and 0.64 for Muguga, cattle close to buffalo, Kibaha, Njombe, Lushoto and Buffalo populations, respectively. The Buffalo and Lushoto isolates possessed a close degree of diversity in terms of mean number of different alleles, effective alleles, private alleles and expected heterozygosity. The study revealed more diversity in buffalo isolates and further studies are recommended to establish if there is sharing of parasites between cattle and buffaloes which may affect the effectiveness of the control methods currently in use.